AN ALTERNATIVE MECHANISM OF FLOOD BASALT FORMATION - King S.D.; Anderson D.L. (My University, 1995)
All large continental igneous provinces and most high-temperature magmas (picrites, komatiites) are found on the margins of cratonic lithosphere. The standard plume model of flood basalt formation offers no explanation for this observation. We propose that thick lithosphere (usually Archean) adjacent to thinner lithosphere may control the locations of flood basalt provinces. The boundary between thick and thin lithosphere focuses both the strain in the lithosphere and the upwelling convection. In addition, the non-uniform boundary condition actually induces a small-scale form of convection that is not present in simple convection and plume models. Whereas plumes are a form of convective instability rising from the base of a convecting system heated from below, the form of convection we are discussing is triggered from above. Unlike other lithospheric mechanisms, the asymmetric lithosphere does not require convective thinning or heating of the plate in order to produce melting. This eliminates time delay between the arrival of the plume head and the onset of volcanism in the stretching model. We consider a series of calculations with a step-function change in thickness of the boundary layer and an externally imposed pull-apart. The flow in our models is shallow and sub-horizontal, and brings hot material from under the thicker (cratonic) boundary layer towards the pull-apart. A simple estimate of the amount of melt generated by this mechanism suggests that it is capable of producing a large igneous province, even for a dry mantle.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей